Mechanized Driving Test System in RTO Office - G. Giri Sai Venkat Niranjan, Y.Bhaskarrao (International Journal of Advanced Science and Technology, 2020)
Now a day the occurrence of road accidents has been frequently increased leading to the death of many people across India. The increase in the use of vehicles increased traffic and unskilled drivers who received their license by simply paying bribe to the Regional Development Officer (RTO) or to the agents. In this paper we are proposing an effective mechanized driving test system. This is more efficient than the existing method because it eliminates human intervention thereby eliminates biased results. This proposed method reduces the road accidents by selecting highly qualified drivers. This driving test system is based on microcontroller, which gives voice commands to the driver and receives the information from IR sensor. This information is calculated and the result is displayed in the LCD.